Relevansi Pemikiran Pendidikan Al-Farabi (872-950) Terhadap Pengembangan Sistem Pendidikan Islam Pada Era Kontemporer - Uci Rahmadini; Maragustam Siregar (4, 2026)
This research focuses on the study of Al-Farabi's educational thought and its relevance in the context of contemporary Islamic education. Using qualitative methods through a literature study approach, this research places Al-Farabi's monumental work, Iḥṣā’ al-‘Ulūm, as the primary source of analysis. Al-Farabi's thought is comprehensively examined through three main aspects: his intellectual background, the construction of the educational framework he offered, and the significance of his ideas for the development of Islamic education in the modern era. As a great philosopher dubbed the second teacher after Aristotle, Al-Farabi succeeded in synthesizing the Greek philosophical tradition with Islamic intellectual and spiritual values. He formulated a hierarchical and systematic educational curriculum system, starting with mastery of language as a tool of thought, continuing with logic, mathematics, natural sciences, metaphysics, and civil sciences such as politics, jurisprudence, and theology. The results of this study demonstrate Al-Farabi's view that education must develop gradually towards intellectual and moral perfection. According to Al-Farabi, the ultimate goal of education is to achieve true happiness (sa'ādah), a state of human perfection realized through the harmony of reason, morality, and action. This concept has strong relevance to contemporary Islamic education, particularly in the effort to shape the perfect human being (insān kāmil), balancing rationality and spirituality, and responding to global challenges through mastery of science and technology based on ethics. Thus, Al-Farabi's educational philosophy makes a significant contribution to strengthening the paradigm and practice of modern, holistic, values-oriented Islamic education. Abstrak Penelitian ini berfokus pada kajian pemikiran pendidikan Al-Farabi serta relevansinya dalam konteks pendidikan Islam kontemporer. Dengan menggunakan metode kualitatif melalui pendekatan studi pustaka, penelitian ini menempatkan karya monumental Al-Farabi, Iḥṣā’ al-‘Ulūm, sebagai sumber utama analisis. Pemikiran Al-Farabi dikaji secara komprehensif melalui tiga aspek utama, yaitu latar belakang intelektualnya, konstruksi kerangka pendidikan yang ia tawarkan, serta signifikansi gagasannya bagi pengembangan pendidikan Islam di era modern. Sebagai seorang filsuf besar yang dijuluki guru kedua setelah Aristoteles, Al-Farabi berhasil mensintesiskan tradisi filsafat Yunani dengan nilai-nilai intelektual dan spiritual Islam. Ia merumuskan sistem kurikulum pendidikan yang bersifat hierarkis dan sistematis, dimulai dari penguasaan bahasa sebagai alat berpikir, dilanjutkan dengan logika, matematika, ilmu-ilmu alam, metafisika, hingga ilmu-ilmu sipil seperti politik, fikih, dan teologi. Hasil penelitian ini menunjukkan pandangan Al-Farabi bahwa pendidikan harus berkembang secara bertahap menuju kesempurnaan intelektual dan moral. Menurut Al-Farabi, tujuan akhir pendidikan adalah mencapai kebahagiaan sejati (sa‘ādah), yaitu kondisi kesempurnaan manusia yang terwujud melalui harmonisasi antara akal, akhlak, dan tindakan. Konsep ini memiliki relevansi yang kuat dengan pendidikan Islam kontemporer, khususnya dalam upaya membentuk manusia paripurna (insān kāmil), menyeimbangkan rasionalitas dan spiritualitas, serta merespons tantangan global melalui penguasaan sains dan teknologi yang berlandaskan etika. Dengan demikian, filsafat pendidikan Al-Farabi memberikan kontribusi penting bagi penguatan paradigma dan praksis pendidikan Islam modern yang holistik dan berorientasi pada nilai.